Evaluation of a general CFD-solver for a micro-scale urban flow. (8th February 2011) - Saloranta, Jarkko; Hellsten, Antti
In this work, we carry out CFD-simulations of the Mock Urban Setting Test (MUST) case in the framework of the COST action 732. The main objective is to assess the quality assurance protocol and guidelines constructed in the COST action 732, and to study the role of the numerical truncation error as part of the total error. The computations are performed with a general flow solver FINFLO. The steady-state RANS approach is used with k-ε and k-ω SST turbulence models. In the near-wall region, standard Wall-Function Approach (WFA) is employed and the tracer is modelled as a passive scalar. The CFD results are compared to wind-tunnel data.